2007
DOI: 10.1075/aila.20.08gaz
|View full text |Cite
|
Sign up to set email alerts
|

Assessing efficiency and fairness in multilingual communication

Abstract: The comparison between various language policies that aim to manage multilingual communication ought to rely on some robust methodology for evaluation. This paper discusses the possibility to found such a methodology on the well-established concepts of efficiency and fairness. Assessing efficiency implies comparing how resources are allocated under alternative policy options (or scenarios) in order to identify the policy promising the best overall allocation. Assessing fairness calls for the evaluation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Presumably, proposals for compensatory transfer payments from Anglophone to non‐Anglophone countries (e.g. Gazzola and Grin 2007; Van Parijs 2007), would gain greater purchase if it could be shown that perceptions of unfair disadvantage were deep‐rooted and widespread. The third question, meanwhile, does not ask about perceptions of disadvantage in general but instead invites respondents to reflect on whether in their own work they feel more advantaged than disadvantaged by the dominance of English.…”
Section: The Study: Context and Purposementioning
confidence: 99%
“…Presumably, proposals for compensatory transfer payments from Anglophone to non‐Anglophone countries (e.g. Gazzola and Grin 2007; Van Parijs 2007), would gain greater purchase if it could be shown that perceptions of unfair disadvantage were deep‐rooted and widespread. The third question, meanwhile, does not ask about perceptions of disadvantage in general but instead invites respondents to reflect on whether in their own work they feel more advantaged than disadvantaged by the dominance of English.…”
Section: The Study: Context and Purposementioning
confidence: 99%
“…Policy evaluation criteria must be adapted to the needs of language policy and planning (LPP). Building on earlier theoretical models, Gazzola and Grin () and Gazzola () design a general framework to evaluate language policies on the basis of policy analysis, focusing on the management of multilingual communication in linguistically diverse organisations such as the EU. The effectiveness of a language policy is assessed in terms of its capacity to ensure effective communication, that is, a way of handling multilingual communication that positively affects the effectiveness of the organisation analysed in achieving its goals.…”
Section: The Evaluation Of Language Regimes: Theoretical Issuesmentioning
confidence: 99%
“…Evaluating the distributive consequences of language policies requires three steps (Gazzola and Grin ), that is: (i) defining the groups concerned – typically, these groups are identified on the basis of the first language (or ‘mother tongue’) of its members; (ii) identifying the channels through which distribution of resources occurs; and (iii) if possible, providing a quantitative estimation of the magnitude of these distributional effects.…”
Section: The Evaluation Of Language Regimes: Theoretical Issuesmentioning
confidence: 99%
“…The analysis of Table 2 shows that the portal is ready to support content in additional languages that are not currently represented in the pool of educational resources available through the portal, such as Arabic, Chinese, Hindi, and other languages, for which the translations of both the user interface as well as the metadata AP and the ontology have already been provided. However, due to the fact that the localization of both the user interface and the content is a time-consuming and costly process, the real needs of the users have to be carefully identified and studied before the localization takes place [12]. This work aims to identify the behaviour of users from specific developing countries, which may contribute to understanding the multilinguality needs of these users.…”
Section: A the Organicedunet Case Studymentioning
confidence: 99%